PERANCANGAN DAN IMPLEMENTASI WEB SERVICE SEBAGAI MEDIA PERTUKARAN DATA PADA APLIKASI PERMAINAN - Zaman, Gilang Arsya Priyatna (Jurnal Informatika, 2017)
Data storage in internal smartphones for an applications game that can be played by many users certainly is not something that is recommended. Base on the problem, it is required a useful application as a provider of the data / messages for the application game. Then the web service is one solution, that can be serves as a bridge between applications and the database. So with the web service will ease the loads on the application, because the exchange of data has been provided by the web service. This paper focuses on implementing web service as a media of exchange data on the game application and the testing using application postman.Keywords: web service, client-server, postman, JSON.